2021
DOI: 10.1111/cch.12911
|View full text |Cite
|
Sign up to set email alerts
|

Maternal resources for care are associated with child growth and early childhood development in Bangladesh and Vietnam

Abstract: Background: Suboptimal child growth and development are significant problems in low-and middle-income countries. Maternal resources for care may help to improve growth and development. This study examined the association of maternal resources for care on child length, motor development and language development of children 12-23.9 months old. Methods: We used baseline data from the Alive & Thrive household surveys collected in Bangladesh (n = 803) and Vietnam (n = 635). Resources for care were represented by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For instance, a study in Uganda found that social support from family and community members was positively associated with child nutritional status [48]. Similarly, a study in Bangladesh found that maternal support was positively associated with child growth [49]. The present study adds to this body of research by providing evidence of the specific types of social support that are most strongly associated with child stunting.…”
Section: Social Supportmentioning
confidence: 53%
“…For instance, a study in Uganda found that social support from family and community members was positively associated with child nutritional status [48]. Similarly, a study in Bangladesh found that maternal support was positively associated with child growth [49]. The present study adds to this body of research by providing evidence of the specific types of social support that are most strongly associated with child stunting.…”
Section: Social Supportmentioning
confidence: 53%
“…However, more studies covering the South Asian region should be conducted to investigate the association of SEP with motor development because diversity of study setting may influence the findings. For example, Basnet et al's (2022) study in Bangladesh did not report any significant associations between SEP and children's motor development (aged 12–24 months).…”
Section: Discussionmentioning
confidence: 95%
“…For example, Basnet et al's (2022) study in Bangladesh did not report any significant associations between SEP and children's motor development (aged 12-24 months).…”
Section: Motormentioning
confidence: 93%
“…For instance, a study in Uganda found that social support from family and community members was positively associated with child nutritional status [ 49 ]. Similarly, a study in Bangladesh found that maternal support was positively associated with child growth [ 50 ]. The present study adds to this body of research by providing evidence of the specific types of social support that are most strongly associated with child stunting.…”
Section: Discussionmentioning
confidence: 99%